Multi-walled carbon nanotubes modified screen-printed electrodes for cisplatin detection - Materon, Elsa M. [UNESP]; Wong, Ademar [UNESP]; Klein, Stanlei I. [UNESP]; Liu, Juewen; Sotomayor, Maria D. P. T. [UNESP] (Elsevier B.V., 2015)
A screen printed electrode functionalized with multi-walled carbon nanotubes and factory modified with carboxyl groups (MWCNT-COOH/SPCEs) was characterized by cyclic voltammetry and differential pulse voltammetry in a NaCl (0.1 mol L-1, pH 7) solution containing 800 mu mol L-1 sodium dodecyl sulfate (SDS). The MWCNT-COOH/SDS/SPCEs sensor was tested for the detection and quantification of cisplatin. For solutions of cisplatin, the electrochemical analysis showed a linear correlation coefficient of 0.9974 to cisplatin at concentrations between 1.45 x 10(-5) and 1.0 x 10(-4) mol L-1, a sensitivity of 4.4 x 10(4) (+/- 1.0 x 10(3)) mu A L mol(-1), and detection and quantification limits of 4.6 x 10(-6) and 1.4 x 10(-5) mol L-1, respectively. The reproducibility of the sensor response evaluated by the analysis of three replicates, indicated a RSD of 3.91%. The excellent response of the MWCNT-COOH/SDS/SPCEs cisplatin sensor allowed it to be tested in samples of human blood serum whose levels of added cisplatin were monitored by the HPLC. The average error % (sensor/HPLC) of 3.4 indicates that the combined methodology of MWCNT-COOH modified SPCE and the addition of a surfactant such as dodecyl sulfate is a convenient alternative for the use of HPLC for cisplatin determination in biological samples. The methodology cannot be applied to non-ionizable antitumor drugs carboplatin, oxaliplatin, doxorubicin or gemcitabine. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Screen printed electrode; Cisplatin; Multi-walled carbon nanotubes (MWCNT-COOH); Sodium dodecyl sulphate (SDS); Differential pulse voltammetry